Effectiveness of Palbociclib in Reducing Cell Multiplication in Human and Mouse Breast Cancer Cell Lines - DAVID GANNON; SHYAMAL K. MAJUMDAR (International Journal of Pharma and Bio Sciences, 2016)
Palbociclib, a recently developed anti-cancer drug was evaluated to determine its effects on the cell proliferation patterns in vitro in two human breast cancer cell lines namely, MCF-7 (Estrogen Receptor positive) and MDA-MB-231 (Estrogen Receptor negative), and in one mouse breast cancer cell line, 4T1 (Estrogen Receptor positive). Approximately, 100,000 cells in two ml of culture medium in each well of 6-well plates were incubated with Palbociclib dissolved in dimethyl sulfoxide (DMSO) at 24-hour intervals for 24 to 96 hours at concentrations ranging from 62.5 nM to 1μM. The control received an appropriate amount of DMSO without Palbociclib. The numbers of viable and dead cells in each culture were recorded every 24 hours using the Trypan blue exclusion assay. The drug inhibited cell replication significantly (Student’s t-test) in the majority of drug concentrations and durations in both human and mouse breast cancer cells. Increasing the concentrations of Palbociclib resulted in decreased rates of cell proliferation, which was found to be significant in most instances. In general, MCF-7 ER positive cells showed slightly more sensitivity, especially at lower concentrations of Palbociclib than MDA-MB-231 ER negative cells; however, these differences were found to be non-significant in most data points. The mouse cells generally exhibited less sensitivity to the drug. The percentage of viable cells treated with different concentrations of Palbociclib was comparable to those of control groups, suggesting the cytostatic mode of inhibitory action.